Influence of Walking, Jogging and Running Exercises Moderates the Selected Lipids and Lipoproteins on Middle Aged Men - K. SekarBabu1, Suthakar Krishnaswamy1, AnnidaBalakrishnan2, B. Parthiban1* (Recent Research in Science and Technology, 2010)
Active life style is the essential requirement for an individual to preserve the well desired health and wellness. Though there is no consensus on the concept of active lifestyle, physical educationists all over the world are trying to find out various means and methods to protect the health of individuals through active life style elements. The present study is aimed to achieve the effect of walking, jogging and running exercises on selected lipids and lipoprotein parameters which normally are considered as risk factors in the Coronary Heart Disease in middle-aged men in the age of 35 to 40 years. Forty men subjects of teaching and non teaching staffs were assigned to four groups, Department of Physical Education and Sports Sciences, Annamalai University. Selected subjects were three experimental groups and one control with ten members in each group. They are Group I as control, Group II as walking; Group III as jogging and Group IV as running. The duration of experimental period is 3 months (3 days /week).Walking; jogging and running exercises were performed by the experimental groups whereas the control remain as normal with the sedentary life. The Training Programme is scheduled by the research scholar of the Physical Education Department. Selected Biochemical variables such as Total cholesterol, Triglycerides, HDL and LDL were analyzed before and after the training period. Biochemical analysis was done by the concerned Biochemist, Department of Biochemistry, Rajah Muthiah Medical College, Annamalai University. Data were collected and statistically analyzed using ANOVA and DMRT. The resulting data revealed that 12 weeks of walking, jogging and running exercises were found to be benefitted in modifying the lipids and lipoprotein levels among middle aged men compared to control. It is predominantly effective in running men than other exercise groups. Hence the study concluded that running exercise prevails in retaining the normal healthy body and obstruct from various coronary heart diseases.